Tobacco harm reduction in Afghanistan: a recipe for improving smokers' health - Attaullah Ahmadi; Ali Rahimi; Mohammad Faisal Wardak; Hamidullah Ahmadi; Don Eliseo Lucero-Prisno (BMC, 2023)
Abstract Tobacco Harm Reduction (THR) offers a promising approach to addressing the significant burden of smoking in Afghanistan. Over three million Afghans smoke daily, making it a leading cause of preventable deaths in the country. While the previous Afghan government implemented various tobacco cessation policies and strategies, these measures were only partially effective in reducing the number of smokers or smoking-related deaths. In 2021, community-based initiatives in Kabul and Herat started advocating for Tobacco Harm Reduction (THR) as a novel, realistic, and practical approach proven to promote smoking abstinence and minimize tobacco harm. However, implementing THR strategies in Afghanistan faces numerous challenges, including a lack of governmental support, funding issues, unfavorable market conditions, the high cost-effectiveness of THR products, and misconceptions about these products. To effectively promote THR in Afghanistan and overcome these challenges, it will be necessary to implement THR policies that support THR products for smokers, regulate the market for these products, produce them locally with healthcare professional oversight, conduct more engaging advocacy campaigns, and secure domestic sponsors.